Landscape enhancement and river preservation. The case of the Aniene River in Rome, Italy - Cialdea, Donatella; Massera, Fabio (TeMA - Journal of Land Use, Mobility and Environment, 2025)
The objective of this study is to integrate the concepts of landscape restoration with the improvement of river areas. Often, there is a coexistence of elements of significant natural value and highly impacting artificial elements, such as large road and railway infrastructures, along watercourses. These elements have altered the landscape value and the usability of the places over time. The ’Landscape Project’, as defined by current Italian landscape legislation, facilitates the implementation of measures aimed at enhancing environmental quality. Concurrently, River Contracts, a novel participatory tool, enable the execution of shared governance strategies designed to upgrade river basins and their associated territories. The case study focuses on the Aniene River, situated in a region of Rome adjacent to the Rome Ring Road. A project evaluation methodology is proposed for this study, which could be considered innovative. The methodology is evaluated through the presentation of results quantifying the benefits of the proposed project actions in terms of pollutant recovery and social welfare.